Poplarism - Lansbury, Edgar (London : Independent Labour Party)
1924 1924 1920s 8 pages (b) Because to bring the working members of the household down to the same level of destitution as his unemployed relatives destroys all "incentive to work" ; (c) Because to try to enforce such a policy would tend to drive the earning members out of the house altogether, thus "breaking up the home"; (d) Because it seems a pity to take from a worker the whole of that proportion of his earnings which he has been able to get from his employer; (e) Because every boy and girl wants to get a little pleasure and excitement out of life; they want to go to the pictures and to football matches, and for country walks; and they cannot do any of these things if every penny of their money is taken to pay industry's debt to their unemployed brothers and sisters. (f) You cannot hold a man responsible for the unemployment of his able-bodied father, sisters or brothers; (g) Because, in any case, the ordinary worker is paid less than enough to live on decently, even if single, and should not be compelled by Guardians of the Poor to live on less than his wages. POPLAR AND THE LABOUR GOVERNMENT. Many members of the Poplar Board work at the docks and on the railways and receive less in wages than the scale of relief which they pay to their unemployed fellow workers. They are not merely recalcitrant, they do not want unhealthy publicity, and they do not want to put the Labour Government in a false position. They want to go on with their work. They know that in Mr. Wheatley they have a Health Minister who will put health before economy; they know that he will understand and sympathise with them in the horrible problem of poverty, misery and distress which faces them. They will still carry on their work of feeding the hungry, and clothing the naked; they will comfort the aged sick in their affliction. They will still care for the widow and the fatherless. Much of the money for this work must be taken from those who want to forget what capitalist society costs the working masses; Poplar's message to them is that whosoever would save his soul must first lose his money. Write to the Head Office of the Independent Labour Party, Headland House, 308 Gray's Inn Road, London, W.C.1, for particulars of the work of the Party, and how you may join it. The Secretary will also be glad to send you, post free, a list of interesting Pamphlets and Books on Socialism and Labour Questions. National Labour Press. Ltd., 17-23, Albion Street, Leicester. — 14372 15X/2/209/47